Wolverine origin : the complete collection - Gillen, Kieron 1975-; Quesada, Joe 1962-; Jenkins, Paul 1965- (Marvel Worldwide, 2018)
"The full story of Marvel's most mystery-shrouded mutant, revealed at last! Long before he became an X-Man, before he was transformed by Weapon X, he was a boy named James Howlett. But what tragedy could strike that would set him on the path to becoming the ferocious Wolverine? Follow young James from a life of privilege and that fateful fi rst "snikt," through the devastating events that rip him from his family and ultimately drive him into the wilderness. There, in the snowy wilds of Canada, the feral young man now known as Logan will encounter another mutant very much like him, also torn between man and animal. One who could be his greatest ally - or his fiercest foe."--Amazon.com
"Contains material originally published in magazine form as Wolverine: The Origin #1-6 and Origin II #1-5"--Title page verso
Keywords: Wolverine -- Fiktive Gestalt; Comic books, strips, etc / United States; Wolverine (Fictitious character); Comic